The Body-Clock Diet - Baker, Sideny M.,Dr. and Baar, Karen (London Vermilion, 2000)
This programme is not a radical diet, it rests upon the theory that we should eat to suit our day and night rhythms. Based on over 20 years of research, the authors suggest by timing our consumption of protein (morning) and carbohydrates (evening) we can control our weight and prevent disease.
Include Index, Glossary and Notes
Keywords: Reducing diets -- Menstrual cycle -- Biological rhythms